EFEKTIVITAS SOCIAL MEDIA ADVERTISING: PERAN BRAND FAMILIARITY DAN KONGRUENSI ENDORSER - Kusumasondjaja, Sony (Jurnal Manajemen dan Kewirausahaan, 2014)
This study examined the impact of brand familiarity and endorsers’ congruence with product being advertised on consumer responses to social media advertising in Twitter. Findings suggested that the product with a familiar brand endorsed by celebrity with high image congruence led to greater consumer trust, more positive attitude, and greater purchase intention than any other familiarity-congruence combinations. Interestingly, for unfamiliar brand, there is no significant difference between high and low endorsers’ congruence.